2017
DOI: 10.25300/misq/2017/41.3.03
|View full text |Cite
|
Sign up to set email alerts
|

User Compensation as a Data Breach Recovery Action: An Investigation of the Sony PlayStation Network Breach

Abstract: Drawing on expectation confirmation research, we develop hypotheses regarding the effect of compensation on key customer outcomes following a major data breach and consequent service recovery effort. Data were collected in a longitudinal field study of Sony customers during their data breach in 2011. One hundred forty-four customers participated in the two-phase data collection that began when the breach was announced and concluded after reparations were made. Using polynomial modeling and response surface ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
136
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(166 citation statements)
references
References 79 publications
15
136
0
Order By: Relevance
“…Particularly interesting in this regard is that the previously mentioned work of Haesevoets, Van Hiel, Onraet, et al () on low‐price guarantees showed, across a set of four empirical studies, that overcompensating price differences in fivefold is not more effective to enhance customer loyalty than equally compensating price differences. In line with the results of this recent study (and those of various other compensation studies; e.g., see Estelami & De Maeyer, ; Garrett, ; Haesevoets, Van Hiel, Pandelaere, et al, ; Noone & Lee, ; for a meta‐analysis, see Gelbrich & Roschk, ; for a recent field study, see Goode, Hoehle, Venkatesh, & Brown, ), the present findings indicated that, in general, large overcompensation does not improve customer loyalty beyond the level that is already reached by equal compensation. Given the high incremental costs of large overcompensation and its lack of positive effects, overcompensation can be considered a cost‐ineffective business strategy for companies to enhance loyalty.…”
Section: Discussionsupporting
confidence: 91%
“…Particularly interesting in this regard is that the previously mentioned work of Haesevoets, Van Hiel, Onraet, et al () on low‐price guarantees showed, across a set of four empirical studies, that overcompensating price differences in fivefold is not more effective to enhance customer loyalty than equally compensating price differences. In line with the results of this recent study (and those of various other compensation studies; e.g., see Estelami & De Maeyer, ; Garrett, ; Haesevoets, Van Hiel, Pandelaere, et al, ; Noone & Lee, ; for a meta‐analysis, see Gelbrich & Roschk, ; for a recent field study, see Goode, Hoehle, Venkatesh, & Brown, ), the present findings indicated that, in general, large overcompensation does not improve customer loyalty beyond the level that is already reached by equal compensation. Given the high incremental costs of large overcompensation and its lack of positive effects, overcompensation can be considered a cost‐ineffective business strategy for companies to enhance loyalty.…”
Section: Discussionsupporting
confidence: 91%
“…In the financial industry, which is the object of our study, in July 2017, a data breach on Equifax, one of the largest credit bureaus in the U.S., exposed the personal and financial information of more than 140 million American consumers, which was more than 55% of the adult population of the United States at that time (Census, 2017). These large-scale data breaches can be quite costly for a company's customer perceptions in the marketplace (Goode, Hoehle, Venkatesh, & Brown, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Belief was measured using a two-item Likert scale. We measured our second dependent variable, intention to share, using a two item 7-point Likert scale adopted and modified from intention to share knowledge [47] and repurchase intention [48] surveys. All scales, definitions and demographics summary have been reported in Appendix (section 7)…”
Section: Methodsmentioning
confidence: 99%